Acid Dentin Lysates Increase Amelotin Expression in Oral Epithelial Cells and Gingival Fibroblasts - Jila Nasirzade; Zahra Kargarpour; Layla Panahipour; Reinhard Gruber (Applied Sciences, 2021)
Amelotin (AMTN) is a secretory calcium-binding phosphoprotein controlling the adhesion of epithelial cells to the tooth surface, forming a protective seal against the oral cavity. It can be proposed that signals released upon dentinolysis increase AMTN expression in periodontal cells, thereby helping to preserve the protective seal. Support for this assumption comes from our RNA sequencing approach showing that gingival fibroblasts exposed to acid dentin lysates (ADL) greatly increased AMTN expression. In the present study, we confirm that acid dentin lysates significantly increase AMTN in gingival fibroblasts and extend this observation towards the epithelial cell lineage by use of the HSC2 oral squamous and TR146 buccal carcinoma cell lines. AMTN immunostaining revealed an intensive signal in the nucleus of HSC2 cells exposed to acid dentin lysates. Acid dentin lysates mediate their effect via the transforming growth factor (TGF)-β type 1 receptor kinase as the antagonist SB431542 abolished the expression of AMTN in the epithelial cells and fibroblasts. Similar to what is known for fibroblasts, acid dentin lysate increased Smad-3 phosphorylation in HSC2 cells. HSC2 cells also respond to the AMTN-stimulating activity of the dentin lysate when adsorbed to gelatin. When simulating regenerative approaches, enamel matrix derivative, TGF-β1, and bone morphogenetic protein-2 also caused a robust increase in SB431542-dependent AMTN expression in HSC2. Taken together, we show here that acid dentin lysate uses the TGF-β-depended signaling pathway to support the AMTN expression in epithelial cells, possibly helping in maintaining the protective seal against the oral cavity.